THE POTENTIAL OF BANANA TRADING COMMODITY TO FULFILL MARKET DEMAND AND SUPPORT FOOD SECURITY IN DEFENSE ECONOMIC PERSPECTIVE (STUDY IN BOGOR DISTRICT) - Indriana Sulistyowarni; Sri Sundari; Supandi Halim (Indonesia Defense University, 2020)
In order to maintain food security, it is wiser if the food priority is not limited to rice, but also encourages product diversity of local food-based such as maize, cassava, sweet potato, breadfruit, taro, and banana. The problems of utilizing banana potential in Bogor District are low production due to land use change, plant function change, some farmers have perception of bananas as a second class plant, Fusarium wilt disease, limited use of bananas as fresh fruit and small industrial processed products (such as chips, sale, molen), and production has not been able to fulfill market demand and consequently, export market opportunities have not been utilized. This study describes the extent to which large potential of banana can be used optimally by using defense economics, demand-supply, and food security theory. Primary data sources were obtained from interviews with informant from Local Government, farmers and banana traders in Bogor District, Ministry of Agriculture, Ministry of Trade. Secondary data sources include both from Ministry, Distanhorti, Disdagin, BPS, journals, and electronic media. Validation data by triangulation and data analysis of Miles-Huberman. The results show that bananas have great potential to be developed in Bogor District but its utilization is not optimal. This is due to several factors including application of inappropriate cultivation techniques with SOP, limited large-scale land, land conversion, without large company partnerships. Therefore, it is necessary to build partnerships with large private companies, synergies and coordination between stakeholders in order to increase bananas potential as trade commodity, hence can fulfill market demand. In the end it will improve economic security as one of the main focuses of the defense economy.Keywords: Banana, Defense Economy, Demand, Food Security, Potential